2019
DOI: 10.3390/su11092524
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Development of Financial Inclusion: How Can Monetary Policy and Economic Fundamental Interact with It Effectively?

Abstract: It is necessary to analyze the relationship between financial inclusion and circumstances-monetary policy and economic fundamentals, which has a practical reference value for policy makers. This paper studies the impact of the circumstances on financial inclusion factors by using a vector autoregressive method. Empirical results show that monetary policy has a short-term positive impact on financial inclusion factors, while the economic fundamental has the opposite, which means that the positive monetary polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 40 publications
2
32
2
Order By: Relevance
“…This is an indication that it becomes imperative to investigate the influence of financial inclusion on the achievement of sustainable development in developing countries, most especially Sub-Saharan African (SSA) countries which is noted for having a large share of the world's vulnerable population. In reference to "sustainable development goals" (SDG), provision of financial inclusion will give support to vulnerable populations to have equal opportunities, assist them in reducing poverty which will bring about reduction in social inequality and eventual achievement of sustainable development (Yin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is an indication that it becomes imperative to investigate the influence of financial inclusion on the achievement of sustainable development in developing countries, most especially Sub-Saharan African (SSA) countries which is noted for having a large share of the world's vulnerable population. In reference to "sustainable development goals" (SDG), provision of financial inclusion will give support to vulnerable populations to have equal opportunities, assist them in reducing poverty which will bring about reduction in social inequality and eventual achievement of sustainable development (Yin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As evidenced in our results, a mature and effective financial development would encourage women to be meaningfully engaged in economic activities by giving them access to useful and affordable financial products and services that meet their needs, including effective payment system, savings, credit and insurance services in a responsible and sustainable way. Meanwhile, for financial inclusion to be more meaningful and to improve the level of African women economic participation, the development of financial inclusion sustainability would deserve more attention (Yin, et al, 2019). This is because most African regions are without sufficient financial resources, and financial inclusion can play an important role in income growth and industrial gender balance that would enhance female labour force participation.…”
Section: Research Resultsmentioning
confidence: 99%
“…Further, Kim et al (2018) reported the relationship of economic growth in the Organization of Islamic Cooperation Countries (OIC) with financial inclusion. Ninth, in a recent study, Yin et al (2019) reported that financial inclusion had debated into two different segments of academia: several studies have been done on the measurement of financial inclusion index with state- or territorial-level data (Adalessossi and Kaya, 2015; Ambarkhane et al , 2016; Kumari, 2017; Sarma, 2008); and other scholars explored the relationship between financial inclusion and economic development factor (Boukhatem, 2016; en et al , 2012; Hassan et al , 2011; Kim et al , 2018; Naceur and Ghazouani, 2007; Peach et al , 2013; Pearce, 2011; Pradhan et al , 2016; Sarma and Pais, 2011). …”
Section: Literature Reviewmentioning
confidence: 91%